Pengaruh Faktor Internal terhadap Kinerja UMKM - Rumbiati Rumbiati (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2022)
This study purpose to look at the internal factors in influencing MSMEs. Respondents used were 120 respondents, were taken randomly. Data processing with SPSS ver. 21, while the data processing is hypothesis testing. Internal factors which include: entrepreneurial orientation (EO), human capital (HC), and entrepreneurial goals and motives (EGM) have a significant effect on the performance of MSMEs.